Civil rights in American law, history, and politics - Sarat, Austin (Cambridge University Press, 2014)
"To pursue the concept of racial entitlement-even for the most admirable and benign of purposes-is to reinforce and preserve for future mischief the way of thinking that produced race slavery, race privilege and race hatred. In the eyes of government, we are just one race here. It is American." Justice Scalia "It never ceases to amaze me that the courts are so willing to assume that anything that is predominantly black must be inferior ... Because of their distinctive histories and traditions, black schools can function as the center and symbol of black communities, and provide examples of independent black leadership, success, and achievement." Justice Thomas It is widely recognized that the idea of rights is central to America's national identity and its sense of itself.1 So powerful is our attachment to rights that some scholars see the American story as powerfully intertwined with what they label a "myth of rights."2 In this myth of rights perhaps nothing plays as important a role as the history of the mid-twentieth century struggle for civil rights for African-Americans. Brown v. Board of Education is, of course, the key moment in that struggle and it has become one of America's "sacred texts," a decision to which almost everyone pays homage even when they act in ways incompatible with its central premises.3 It is to the spirit of Brown that groups seeking recognition continuously appeal, a spirit that today plays a key role in the debate over gay marriage.4 Civil Rights in the American Story brings together the work of five distinguished scholars to critically assess the place of civil rights in the American story. This work includes examples of both the "old" and the "new" civil rights history. It uses the sources and analytics of both legal and social history"--